Unlocking the M13 (F1) virion : investigation into the role of pIII C domain of F specific filamentous bacteriophage in infection : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Biochemistry at Massey University, Palmerston North, New Zealand - Bennett, Nicholas James (Massey University, 2005)
Filamentous phage adsorb to the host cells by binding of the N2 domain of pIII to the tip of the F pilus. Binding of N1 domain of pIII to the secondary receptor (Tol A), triggers the opening of the virion by a poorly understood mechanism. Filamentous phage assembly is a secretion-like process. The assembly is terminated and virion released from the membranes by C domain of pIII. Because the infection is a reversal of assembly, it can be hypothesized that the C domain of pIII plays an active role in the infection. To test this hypothesis, we have set up a system in which virions carried a mixture of two types of mutant pIII molecules: i) functional N1N2 domains fused to a short C domain that can be incorporated but cannot terminate assembly and release the phage from the membrane: ii) C domain only, which can terminate phage assembly, but lacks the receptor-binding domains N1N2. The infectivity of the particles was as low as 0.21% that of the positive control setup in which virions carried a mixture of wild-type pIII and C domain. Therefore, a functional C domain covalently linked to the receptor domain N1N2 is required for infection. These findings suggest that simple binding of N1 domain of pIII to the periplasmic receptor TolA is not sufficient for infection. Rather, this interaction may, via functional C domain of pIII, trigger a conformational change required for the downstream events which result in the virion uncoating and DNA entry. To add further weight to this model, a "microphage" producing system was designed to produce short phage particles suitable for Cryo-EM structural analysis.
Keywords: Bacteriophages; Genetics